DO FIRMS FACING INCREASES IN FINANCIAL CONSTRAINTS TEND TO GENERATE CASH THROUGH TAX AVOIDANCE? EMPIRICAL EVIDENCE FROM INDONESIA PUBLICLY LISTED FIRMS - John Erhan Prasetyo Hermawan; Riko Riandoko (Scientax, 2021)
This study examines the effect of increases in financial constraints measured at both firm-specific and macroeconomic level on corporate tax avoidance behaviour. Based on a hand-collected sample of 60 publicly listed firms on Indonesia Stock Exchange (IDX) from the year 2009 to 2016, our regression result shows that firms facing increased firm-specific constraints exhibit lower cash effective tax rates ranging from 0.55 to 9.57 percent which equate to between 0.60 and 10.29 percent of operating cash flows, whereas at macroeconomic constraints do not. The firm-specific constraints result is consistent with our hypothesis and Edwards, et al. (2016), whereas macroeconomic constraints result is inconsistent. Nevertheless, its inconsistency can be caused by several factors, i.e.: (1) the change of corporate tax rate from 28 to 25 percent as fiscal policy after the impact of Global Financial Crisis 2008. It could reduce tax avoidance behaviour; (2) Indonesian Go Public Information Centre stated that the purpose of the firms’ Initial Public Offering (IPO) is not only to finance the firms’ operation due to increases in financial constraints, but also to increase firm value, improve corporate image, grow employee loyalty, maintain business continuity and get tax incentives; (3) the equity financing in Indonesia is more related to equity participation activities conducted among shareholders that’s not listed on the stock or bond markets, e.g. private placement, joint venture, mergers and acquisitions.